Kajian Analisis terhadap Kitab Hadith al-Durrah al-Saniyyah Karangan Haji Ismail Bin Omar al-Patani - Muhammad Widus Sempo; Abdulloh Salaeh; Amran Abdul Halim; Syed Najihuddin Syed Hasaan; Idi Hamdi al-Fathoni (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: Prophet Muhammad (PBUH) is one of the Ulul Azmi and being appointed as the leader for the humankind through his speeches, works and other things related to his Sunnah. The main objective of this study is to introduce the prominent Islamic scholar in Hadith, Baba Ismail Sepanjang and his book ‘Al-Durrah Al-Saniyyah’ and to highlight his exceptional contribution in this field. This study relies on many types of approaches including both qualitative and quantitative method. This study finds that Tuan Guru Haji Ismail bin Omar teaches hadith very clear and gives an excellent contribution in the field of hadith for Muslim society in Patani through his writings and his speech.